COVID-19 AND THE DEREGULATION OF THE SUBTRACTION LIMITS OF THE BRAZILIAN WORKERS TIME - Neto, Silvio Beltramelli; Pedroso, Fernando Carmona (Revista de Direito Brasileira, 2023)
This study aims, in the light of the global context and comparative international experiences, to describe and critically examine recent changes in the regulation of the working time in Brazil and its current trends. It is concluded that the deregulation of the limits of the working time had already been rapidly implemented in the world and that, within the context of neoliberalism and technological revolution and, from the point of view of what happened in Brazil, such deregulation was opportunistically deepened with respect to the Covid-19 pandemic. The dialectical materialistic approach method was used for the research, carried out by an eminently bibliographic and statistical procedural methodology.